Identification of Feather Mites on Asian Glossy Starling (Aplonis panayensis) in Industrial Estate - Rahayu, Jasti; Soviana, Susi; Hadi, Upik Kesumawati (Jurnal Sain Veteriner, 2025)
This study aims to identify the types of feather mites found on Asian glossy starling (Aplonis panayensis) (Passeriformes: Sturnidae) as a pest in industrial estate. This issue has not been extensively studied, and information about the feather mites biodiversity of Asian glossy starlings in Indonesia is limited. Feather mites samples were collected from KIE Bontang, East Kalimantan in January 2024. Live traps with mist nests were used to catch Asian glossy starlings and mites were examined on the feathers. Mites specimens preserved in ethanol 70%. Asian glossy starlings then released into the wild after examination. Data analysis and mites identification were conducted in the Health Entomology Laboratory of the School of Veterinary Medicine and Biomedicine at Bogor Agricultural University from July until September 2024. Feather mites were preserved on the microscope slide. Mites observations were used Olympus CX23 microscope with 10x and 40x objective magnifications. Based on identification, feather mites on Asian glossy starlings were described 2 types Astigmata, Trouessartia sp. (Sarcoptiformes: Trouessartiidae), and Montesauria sp. (Sarcoptiformes: Proctophyllodidae) found on the secondary feathers of Asian glossy starling wings. Male Trouessartia sp. was found with patterned shields, like hollow tissue (lacunae) and anterior hysterosomal shield separate from the other shield. Female Montesauria sp. was found with a slender, elongated, and flat body shape, large and sclerotized dorsal body shield, leg I hypertrophied, setae h2 fusiform and spindle-like, filiform setae h3. Trouessartia sp. and Montesauriasp. play an important role in maintaining ecosystem function as symbionts.